Seventh International Conference on Quality Software (QSIC 2007) 2007
DOI: 10.1109/qsic.2007.4385491
|View full text |Cite
|
Sign up to set email alerts
|

A Certified Infinite Norm for the Implementation of Elementary Functions

Abstract: The high-quality floating-point implementation of useful functions f : R → R, such as exp, sin, erf requires bounding the error ε = p−f f of an approximation p with regard to the function f . This involves bounding the infinite norm ε ∞ of the error function. Its value must not be underestimated when implementations must be safe. Previous approaches for computing infinite norm are shown to be either unsafe, not sufficiently tight or too tedious in manual work. We present a safe and self-validating algorithm fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…In fact, in [15] authors of this article tried to use a similar recursive technique, but they observed that the derivative of the error, the second derivative of the error and so on and so forth are all prone to the same phenomenon of very high overestimation. That is why, for higher degree of p (higher than 10) the number of splittings needed to eliminate the correlation problem is still unfeasible.…”
Section: Rigorous Global Optimization Methods Using Interval Arithmeticmentioning
confidence: 99%
“…In fact, in [15] authors of this article tried to use a similar recursive technique, but they observed that the derivative of the error, the second derivative of the error and so on and so forth are all prone to the same phenomenon of very high overestimation. That is why, for higher degree of p (higher than 10) the number of splittings needed to eliminate the correlation problem is still unfeasible.…”
Section: Rigorous Global Optimization Methods Using Interval Arithmeticmentioning
confidence: 99%
“…In addition, the polynomial is an approximation to the sine function, with a relative error bound of ǫ approx which is supposed known (how it was obtained it is out of the scope of this paper [18]).…”
Section: Example: a Double-double Polynomial Evaluationmentioning
confidence: 99%
“…This rigor is achieved through an extensive use of Interval Arithmetic [9], extended to cover functions with false singularities [4]. Interval Arithmetic is of course available at the Sollya interface, too.…”
Section: Key Features Offered By Sollyamentioning
confidence: 99%
“…-Supremum norms of approximation error functions: Sollya can compute safe bounds on the supremum norm of the error ε = p/f − 1 made when replacing a function f by a particular polynomial p in a bounded domain I. Such computations are a requirement for code certification for mathematical functions [4]. -Support for code generation in IEEE 754 arithmetic: Sollya offers extensive support for simulating IEEE 754 arithmetic.…”
Section: Key Features Offered By Sollyamentioning
confidence: 99%